Co-creating nutrition-sensitive development pathways with aquatic foods: Consulting local food systems partners in Baucau and Lautem municipalities, Timor-Leste - Bonis-Profumo, Gianna; Alves Almeida, Carlos; Simões, N.; Duarte, Agustinha; Hunnam, Kimberly; Eriksson, Hampus (WorldFish, 2023)
On 23 June 2022, WorldFish held a consultation workshop in Baucau Vila to introduce its planned action research program (Box 1) in Baucau and Lautem municipalities to its diverse partners, including national, municipal and local government representatives, community members, and local and international NGOs. This brief provides a summary of the workshop and demonstrates the first steps towards co-developing a municipality-level food systems coalition for sustainable and nutrition-sensitive transformation that includes aquatic foods.